S113 Predictors Of Bacterial 'load' In Pleural Infection. (10th November 2014) - Wrightson, JM; Wray, JA; Street, TL; Chapman, SJ; Crook, DWM; Rahman, NM
Abstract : Pleural infection is usually defined using pleural fluid biochemical characteristics, given that only ~30% of cases are culture positive, but the relationship between these characteristics and pleural space bacterial concentration is unclear. We developed an assay to estimate bacterial 'load' using quantitative polymerase chain reaction (PCR) to determine 16S rRNA gene copy number in pleural fluid samples (this gene is present in all bacteria). This enabled us to explore the relationship between patient characteristics and pleural fluid bacterial 'load'. Methods: Pleural infection samples were obtained from the Second Multicentre Intrapleural Sepsis randomised controlled Trial (MIST2), REC no. 04/MRE5/53. DNA was extracted using the FastDNA SPIN Kit. Quantitative PCR (qPCR) of the 16S rRNA gene was undertaken using the ultra-pure Power SYBR Green PCR reagent and primers that amplified the 467 nt V3–4 region of the 16S rRNA gene. A 3-step thermal cycling profile was empirically determined to give optimal results. Ten-fold dilutions of Acidothermus cellulolyticus DNA were used to estimate sample 16S rRNA gene concentration. All PCRs were performed in duplicate. Melt-curve analyses and agarose gel electrophoresis of qPCR amplicons were used to ensure absence of non-specific PCR products. Results: 172 pleural fluid samples were analysed. Pleural fluid pH, culture status, appearance, LDH and glucose were all predictive of bacterial load (see Table ). Patient C-reactive protein (CRP) and white cell count (WCC) were not significantly associated with bacterial load. Conclusions: Bacterial 'load' was associated with acknowledged predictors for pleural infection. Such findings add further support to the utility of pH, glucose and LDH values as proxies for pleural infection, in the correct clinical context. Patient WCC and CRP were not significantly associated with bacterial 'load'. This assay is limited in that it assesses total bacterial DNA (from viable and dead bacteria), rather than quantifying viable bacteria. Further, bacteria vary in their copy number of the 16S rRNA gene, dependent on species. Despite these limitations, our associations have reached a strong level of significance.